Abscisic acid may alter the salicylic acid-related abiotic stress response in maize - Szalai, Gabriella; Pál, Magda; Janda, Tibor (Acta Biologica Szegediensis, 2011)
The effect of abscisic acid (ABA) treatment on chilling tolerance and salicylic acid (SA)-related responseswas investigated in young maize seedlings. Although the pre-treatment of plants with ABA slightly decreased the chlorophyll content, it also reduced the level of chilling injury caused by 6 days of cold treatment at 5 ̊C. Under normal growth conditions increased levels of bound SA and of bound ortho-hydroxycinnamic acid (oHCA) were observed in the leaves during ABA treatment. In the roots ABA did not affect the free and bound SA levels, but increased the amount of free and bound oHCA. The activity of glutathione-S-transferase (GST) increased on the 3rd day of ABA treatment, while it did not change when followed by cold stress, compared to the control leaves. In the roots the activities of glutathione reductase, GST and ascorbate peroxidase (APX) increased during the ABA treatment, and those of GST and APX were also stimulated when ABA pre-treatment was followed by cold stress, compared to the control roots. Our results suggest that an overlap may exist between the ABA-induced cold acclimation and the SA-related stress response.